Eight Inuit myths = Inuit unipkaaqtuat pingasuniarvinilit - Spalding, Alex (Inuit unipkaaqtuat pingasuniarvinilit., 1979)
Eight Nassilingmiut (Central Arctic Inuit) myths are given a roughly morphemic translation as well as a literary translation into English with preface and glossary included. (Abstract).